Porous coordination polymer-derived ultrasmall CoP encapsulated in nitrogen-doped carbon for efficient hydrogen evolution in both acidic and basic media. (13th January 2020) - Liu, Shuai; Jiang, Anning; Wang, Zegao; Lin, Mengxia; Xia, Dan; Li, Qiang; Dong, Mingdong
Abstract: Exploiting high-efficient and stable non-precious metal-based electrocatalysts toward hydrogen evolution reaction (HER) is of enormous significance to address the shortage of global power source, but there remain major challenges. Here we present a facile and controllable strategy to synthesize a strongly coupled ultrasmall-cobalt phosphide/nitrogen-doped graphitic carbon (u-CoP@NC) hybrid structure via phosphorization from a porous coordination polymer (PCP) precursor. The PCP-derived u-CoP@NC exhibits remarkable activity and stability for HER, achieving a current density of 10 mA cm −2 with a low overpotential of 131 mV in acidic media and 111 mV in basic media. The corresponding Tafel slopes present in acidic and basic media are 62.7 and 70.3 mV dec −1, respectively. Results reveal that the enhanced electrocatalytic performance of u-CoP@NC originates from the strongly coupled u-CoP nanoparticles and graphitic carbon layer, and the perfect dispersity of the active sites. This research opens up new avenues for designing earth-abundant metal-based electrocatalysts with high capability for water splitting applications. Highlights: u-CoP@NC were directly synthesized through phosphorization of a PCPs precursor. Remarkable electrocatalytic activity of u-CoP@NC towards HER was achieved. The synergistic effect between u-CoP and NC could improve the HER performance. The confinement by NC layers enhanced the stability of the u-CoP@NC catalysts.